2012
DOI: 10.2147/cmar.s31847
|View full text |Cite
|
Sign up to set email alerts
|

The bradykinin B2 receptor induces multiple cellular responses leading to the proliferation of human renal carcinoma cell lines

Abstract: BackgroundThe vasoactive peptide bradykinin (BK) acts as a potent growth factor for normal kidney cells, but there have been few studies on the role of BK in renal cell carcinomas.PurposeIn this study, we tested the hypothesis that BK also acts as a mitogen in kidney carcinomas, and explored the effects of BK in human renal carcinoma A498 cells.MethodsThe presence of mRNAs for BK B1 and BK B2 receptors in A498 cells was demonstrated by reverse transcription–polymerase chain reaction. To study BK signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The mitogenic effect of bradykinin mediated by G protein-coupled B2Rs involving MEK/MAPK is observed in epithelial breast cancer cells [35], bovine tracheal smooth muscle cells [36], and also human renal carcinoma A498 cells [37]. Bradykinin acts as a proliferative agent in MCF-7 cells by activating intracellular pathways including PKC, pAkt and pERK1/2 [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitogenic effect of bradykinin mediated by G protein-coupled B2Rs involving MEK/MAPK is observed in epithelial breast cancer cells [35], bovine tracheal smooth muscle cells [36], and also human renal carcinoma A498 cells [37]. Bradykinin acts as a proliferative agent in MCF-7 cells by activating intracellular pathways including PKC, pAkt and pERK1/2 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated that bradykinin displays a wide range of biological activities in different tissues, including regulation of mitogenesis in several cell types [ 34 ]. The mitogenic effect of bradykinin mediated by G protein-coupled B2Rs involving MEK/MAPK is observed in epithelial breast cancer cells [ 35 ], bovine tracheal smooth muscle cells [ 36 ], and also human renal carcinoma A498 cells [ 37 ]. Bradykinin acts as a proliferative agent in MCF-7 cells by activating intracellular pathways including PKC, pAkt and pERK1/2 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In A549 lung epithelial cells, bradykinin requires G q/11 to activate and MAPK14, which induces the phosphorylation of EGFR at Ser 1047 and upregulates the transcription of dual-specificity MAPK phosphatase 5 (DUSP5) (Izumi et al 2018). Bradykinin mediated B2R activation leads to cell proliferation in renal carcinoma A498 cells through MAPK1/3 and NHE1 pathways (Kramarenko et al 2012). Also, bradykinin/B2R promoted the proliferation, migration, and invasion of cervical cancer cells via the STAT3 signaling pathway by upregulating the expression of MMP-2, MMP-9 and downregulating the expression pro-apoptotic protein cleaved caspase-9 (Yang et al 2009;Wang et al 2019).…”
Section: Cancermentioning
confidence: 99%
“…Kramarenko discovered that bradykinin promotes the proliferation of RCC cells (A498 cell line) through the B2 receptor. This activation is dependent on the PLC, PKC, and ERK pathways, as well as on Ca2+/Cam activity ( 49 ). Thus, the increased concentration of bradykinin observed in ACEI users may promote carcinogenesis and tumor cell proliferation.…”
Section: Effect Of Acei Usementioning
confidence: 99%